Control of DC-DC Buck Converter Based on Adaptive Neuro Fuzzy Inference System (ANFIS) - Syafitri, Muharani; Yuhendri, Muldi (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Various electrical equipment uses direct voltage (DC) as its power source, such as electronic equipment, dc motors and so on. Direct voltage (DC) used in electrical equipment usually consists of various voltage ratings ranging from 1.5 volts, 3 volts, 6 volts 12 volts and others. To get a direct voltage (DC) that suits the needs of the equipment, the direct voltage needs to be controlled. Direct voltage control is usually implemented using a power converter. In this research, the buck converter output voltage control based on Adaptive Neuro Fuzzy Inference System (ANFIS) will be implemented using Arduino Atmega 2560. The buck converter output voltage control system made in this research will be tested through experiments with an input voltage of 24 Volts and a maximum output of 18 Volts. The experimental results show that the ANFIS-based buck converter output voltage control system has been able to control the buck converter output voltage according to the desired reference voltage value.